Analysis and mitigation of stimulated Raman scattering effects in OTDR monitored optical link - Hussein, A.H.; Anas, S.B.A.; Ghazali, M.S.; Amran, R.; Yaakob, S.; Bakar, M.H.A.; Khairi, K.; Ahmad, A.; Ngah, N.A.; Muhd-Yassin, S.Z.; Tee, D.C.; Go, Y.I. (Elsevier, 2024)
The co-existence of both traffic signal and optical time-domain reflectometer (OTDR) signal in active fiber monitoring will affect the dynamic range of the OTDR due to backscattered stimulated Raman scattering (SRS). In this paper, a simulation model and hardware experiment are proposed to investigate and mitigate the effects of a backscattered SRS signal on OTDR active fiber monitoring. A basic OTDR active fiber monitoring system based on non-amplified and amplified links was developed, where the effects of SRS backscattered noise, amplification noise, and power depletion were observed. The obtained simulation results indicated that the highest backscattered SRS was contributed by the booster amplifier link configuration, where the amplification of the OTDR signal increased drastically when the signal input power reached 10 dBm. The simulation setup was also used to mitigate the backscattered SRS by placing a chirped fiber Bragg grating (CFBG) at the OTDR to allow only the 1650 nm OTDR signal to be received by the OTDR, leaving other unwanted signals or noise behind. This mitigation successfully reduced other backscattered signals by approximately 4 dB. A proof-of-concept hardware experiment was conducted to test the feasibility of the proposed technique, and the result showed that the distortion in the trace was decreased and the OTDR penalty was also reduced to 0.41 dB.